Pręt Równej Wytrzymałości przy Drganiach Własnych Pierwszego Rzędu - Łączkowski, R. (Engineering Transactions, 1966)
The paper contains a description of a method for determining the form of a bar clamped at one end and free at the other, and performing natural vibration of the first order and preserving constant stress in the longitudinal direction. The form of such a bar is determined in a dimensionless manner. Some measurement results of dynamic stress distribution are quoted for a real bar.